Bias Perilaku dalam Keputusan Keuangan: Perspektif Ekonomi Perilaku Modern - Yusriza Yusriza; Irhamna Irhamna; Evi Rahayu (Cyber Media Indonesia, 2025)
This study aims to analyze the role of behavioral biases in the process of financial decision-making by employing the perspective of modern behavioral economics. In classical economic theory, individuals are assumed to be rational and capable of consistently maximizing utility. However, various findings in behavioral economics indicate that financial decisions are often influenced by psychological factors, cognitive limitations, and emotions. This article examines several common forms of behavioral biases, such as overconfidence bias, loss aversion, anchoring, and herd behavior, along with their implications for investment decisions, risk management, and financial planning. Through a conceptual analysis based on a review of the literature, this study explains how deviations from rationality can affect the quality of decisions and potentially generate market inefficiencies. In addition, the discussion highlights the relevance of integrating psychological and economic approaches to better understand the dynamics of individual financial behavior. The findings suggest that understanding behavioral biases is essential for improving financial literacy and enhancing the quality of decision-making, both at the individual and institutional levels. Therefore, the modern behavioral economics perspective makes a significant contribution to enriching contemporary financial analysis. Abstrak Penelitian ini bertujuan untuk menganalisis peran bias perilaku dalam proses pengambilan keputusan keuangan dengan menggunakan perspektif ekonomi perilaku modern. Dalam teori ekonomi klasik, individu diasumsikan rasional dan mampu memaksimalkan utilitas secara konsisten. Namun, berbagai temuan dalam ekonomi perilaku menunjukkan bahwa keputusan keuangan sering kali dipengaruhi oleh faktor psikologis, keterbatasan kognitif, serta emosi. Artikel ini mengkaji berbagai bentuk bias perilaku yang umum terjadi, seperti overconfidence bias, loss aversion, anchoring, dan herd behavior, serta implikasinya terhadap keputusan investasi, pengelolaan risiko, dan perencanaan keuangan. Melalui pendekatan analisis konseptual berbasis literatur, studi ini menjelaskan bagaimana penyimpangan dari rasionalitas dapat memengaruhi kualitas keputusan dan berpotensi menimbulkan inefisiensi pasar. Selain itu, pembahasan juga menyoroti relevansi integrasi pendekatan psikologi dan ekonomi dalam memahami dinamika perilaku keuangan individu. Hasil kajian menunjukkan bahwa pemahaman terhadap bias perilaku menjadi penting dalam meningkatkan literasi keuangan dan kualitas pengambilan keputusan, baik pada level individu maupun institusi. Oleh karena itu, perspektif ekonomi perilaku modern memberikan kontribusi signifikan dalam memperkaya analisis keuangan kontemporer.